2016
DOI: 10.1149/2.0091606jes
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrocatalytic Property of PbO2-CeO2Nanocomposite Electrodes by Pulse Reverse Electrodeposition Methods

Abstract: PbO2-CeO2 nanocomposite electrodes were prepared by pulse reverse electrodeposition in the lead nitrate solution containing CeO2 nanoparticles. The effect of pulse reverse electrodeposition parameters, such as reverse pulse frequency, reverse peak current density and reverse duty cycle, on the content of CeO2 nanoparticles in the PbO2-CeO2 nanocomposite electrodes was investigated. The SEM and XRD tests show that PbO2-CeO2 nanocomposite electrodes possess finer grain size than PbO2-CeO2 nanocomposite electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Among MMCs, nickel-based alloys have been widely used in different industrial applications due to their outstanding performance and low cost [1]. Among various fabrication techniques, electrodeposition is one of the most common method of producing various metal matrix coatings [1][2][3][4][5][6][7]. The reinforcing phases (insoluble materials) are suspended in a conventional electrodeposition bath and co-deposited within the metal matrix during the electrodeposition process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among MMCs, nickel-based alloys have been widely used in different industrial applications due to their outstanding performance and low cost [1]. Among various fabrication techniques, electrodeposition is one of the most common method of producing various metal matrix coatings [1][2][3][4][5][6][7]. The reinforcing phases (insoluble materials) are suspended in a conventional electrodeposition bath and co-deposited within the metal matrix during the electrodeposition process.…”
Section: Introductionmentioning
confidence: 99%
“…These insoluble components can be in the form of powder, fiber or encapsulated particles. The electrodeposition of various Ni-based composites has been reported in which one or more of various metallic oxides such as CeO 2 , ZrO 2 , Al 2 O 3 , TiO 2 , MoO 2 and carbides such as SiC were added into Ni-based electrodeposition baths [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Substantial improvements were observed in material properties such as micro-hardness, wear, and corrosion resistance as a result of the co-deposition of reinforcements phase(s) into the Ni matrix [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Yao et al used electrochemical co‐deposition method to dope CeO 2 (Yao, Dong, Jiao, Yu, & He, 2016; Yao et al., 2015, 2018) and ZrO 2 (Yao, Ren, Yang, Huang, & Li, 2019; Yao, Zhao, Zhao, & Zhang, 2014; Yingwu, Chunjiao, Xin, Feng, & Huailiang, 2017) particles into PbO 2 coating and studied the influence of those metal oxide particles on the electrode performance. The results indicated that the doping of CeO 2 and ZrO 2 particles can effectively improve the oxygen evolution over‐potential and strengthen the service life of electrode.…”
Section: Introductionmentioning
confidence: 99%